DreamWorks holiday collection [videorecording (DVD)] (DreamWorks Home Entertainment, 2013)
Shrek the halls: After promising Fiona and the kids a Christmas they will remember and with no clue how to plan anything for the holidays, Shrek is forced to take a crash course in the holiday. Just when he thinks he has everything for their quiet family Christmas just right, Donkey, Puss in Boots, Gingy and the rest of the gang decide to crash the party -- Merry Madagascar: When Santa and his reindeer crash onto the island of Madagascar, it's up to Alex, Marty, Gloria, Melman and those wacky penguins to save Christmas -- Dragons holiday: Gift of the night fury: The Dragons are back in this exciting chapter of Hiccup and Toothless as they take flight in a thrilling, adventure to discover an island of never-before-seen dragons. Explosive action and fire-breathing excitement collide in this exhilarating dragon story -- Kung fu panda holiday: Master Shifu puts Po in charge of hosting the Winter Feast, held to celebrate family and kung fu. Po recruits the Furious Five to help him make the event the best that the Valley of Peace has ever seen.